2021
DOI: 10.4236/jcc.2021.95006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Support Vector Machine and Artificial Neural Network for Option Price Prediction

Abstract: Option pricing has become one of the quite important parts of the financial market. As the market is always dynamic, it is really difficult to predict the option price accurately. For this reason, various machine learning techniques have been designed and developed to deal with the problem of predicting the future trend of option price. In this paper, we compare the effectiveness of Support Vector Machine (SVM) and Artificial Neural Network (ANN) models for the prediction of option price. Both models are teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We likewise believe that our model can be used to solve problems related to regression after a SVM-to-SVR-like transformation (e. g. [12][13][14][15][16][17]). Of particular interest is the fact that our algorithms are well suited for applications in the field of financial forecasting(e. g. [18][19][20].). e field of financial forecasting requires algorithms with controllable computation times and good performance for nonlinear problems.…”
Section: Discussionmentioning
confidence: 99%
“…We likewise believe that our model can be used to solve problems related to regression after a SVM-to-SVR-like transformation (e. g. [12][13][14][15][16][17]). Of particular interest is the fact that our algorithms are well suited for applications in the field of financial forecasting(e. g. [18][19][20].). e field of financial forecasting requires algorithms with controllable computation times and good performance for nonlinear problems.…”
Section: Discussionmentioning
confidence: 99%
“…Neural network and financial markets. Many academics have reported that the neural network is one of the best models to examine many financial concepts and can be used to explore the effects of COVID-19 on stock financial markets [8,[54][55][56][57][58]. [59] showed that algorithms can predict stock market deterioration.…”
Section: Plos Onementioning
confidence: 99%
“…e number of groups, move steps, and number of iterations within groups were mainly simulated to verify the effect of different parameters on the prediction accuracy. e number of hidden layer neurons of the RBF neural network was set to 10 and It can be seen that when the number of groups belongs to [10,20,30,40,50] and the step size [1,3,5], the RMSE does not exceed 0.7, and the maximum and minimum values do not deviate much from the mean value, so the algorithm is relatively stable. In practice, the SFLA parameters can be fine-tuned by changing the main parameters several times in order to achieve better prediction results.…”
Section: Effect Of Sfla Parameters On Gdp Forecastingmentioning
confidence: 99%
“…e human brain can handle a variety of complex non-linear problems very quickly, and researchers have been inspired by the idea of how to simulate the human brain to deal with complex non-linear problems. An artificial neural network (ANN) is an intelligent bionic model that mimics the function of neurons in the brain [18][19][20][21], and is a non-linear complex network system consisting of a large number of interconnected neurons.…”
Section: Introductionmentioning
confidence: 99%